Cultural Security of Ukraine - Krasivskyy, Orest; Pidberezhnyk, Nadiia (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
Condition and problems of ensuring the cultural security of Ukraine were analyzed. Hypothesis that ensuring development and sustainability of the cultural sphere, formation of a single Ukrainian socio-cultural space based on Ukrainian language, historical memory, spiritual values, cultural traditions is one of priority national interests of the Ukrainian state at the present stage was put forward. Research methodology is based on the principles of objectivity and systematicity. During the research, methods of scientific learning of socio-political phenomena and processes were used, in particular: analysis, synthesis, systematization, empirical, and system-structural methods. The authors prove that cultural traditions, historical memory, self-consciousness and language are key factors that constitute and consolidate a nation, and threats to the nation’s cultural interests can jeopardize its existence. It was found that the centuries-old policy of de-ethnicization and assimilation of Ukrainian ethnos by foreign states has led to deformation and russification of the national linguistic and cultural space of Ukraine, loss of ethnic identity based on the language factor of the titular Ukrainian ethnos, deepening the spiritual crisis of Ukrainian society. It is determined that the key threats in the field of cultural security of Ukraine today are the following: Russia’s hybrid war against Ukraine, formation of information and cultural space of Ukraine under the influence of foreign information flows, imperfection of humanitarian policy in the context of cultivating Ukrainian national values, low level of development of cultural industries, dominance of foreign cultural and artistic products, control over Ukrainian media by financial and industrial groups that often take an anti-Ukrainian position. It was proved that the measures to assert and popularize Ukrainian language as the state language, ensure intercultural communication and interethnic socialization of ethnic subjects of Ukrainian society, formation of national-patriotic education, creation of competitive innovative cultural products and their popularization in the world should be priority directions of the state policy of ensuring cultural security of Ukraine.

Artykuł poświęcony został zagadnieniu bezpieczeństwa kulturowego Ukrainy, jego obecnej kondycji oraz zagrożeń. Autorzy stawiają tezę, iż ukraińska racja stanu wymaga zapewnienia rozwoju i trwałości sfery kulturowej państwa, stworzenia jednolitej ukraińskiej przestrzeni społeczno-kulturowej opartej na języku ukraińskim, pamięci historycznej, wartościach duchowych oraz tradycjach kulturowych. Zdaniem autorów, wspomniane powyżej tradycje kulturowe, pamięć historyczna, samoświadomość oraz język są kluczowymi czynnikami konstytuującymi i scalającymi naród, a zagrożenia dla jego interesów kulturowych mogą też zagrażać istnieniu samego narodu. W artykule stwierdzono, iż wielowiekowa polityka wynarodowienia i asymilacji etnosu ukraińskiego przez obce państwa doprowadziła do deformacji oraz rusyfikacji narodowej przestrzeni językowej i kulturowej Ukrainy. Co więcej, w efekcie powyższych procesów doszło do utraty tożsamości etnicznej w oparciu o czynnik językowy części narodu ukraińskiego oraz do głębokiego kryzysu duchowego społeczeństwa ukraińskiego. Za kluczowe zagrożenia w obszarze bezpieczeństwa kulturowego Ukrainy uznano dziś: wojnę hybrydową Rosji z Ukrainą, kształtowanie się przestrzeni informacyjnej i kulturowej Ukrainy pod wpływem zagranicznych kanałów informacyjnych, niski poziom rozwoju ukraińskiego przemysłu rozrywkowego, dominację zagranicznych ośrodków kulturalnych i artystycznych oraz sprawowanie kontroli nad ukraińskimi mediami poprzez podmioty zagraniczne, często reprezentujące antyukraiński punkt widzenia. Wykazano również, że działania na rzecz propagowania i upowszechniania języka ukraińskiego jako języka państwowego, kształtowanie edukacji narodowo-patriotycznej, tworzenia konkurencyjnych i innowacyjnych produktów kultury oraz ich popularyzacja poza granicami Ukrainy powinny stać się priorytetowymi kierunkami państwowej polityki bezpieczeństwa kulturalnego Ukrainy.
Bezpieczeństwo kulturowe Ukrainy
Keywords: culture; cultural security; Ukraine; nation; language; national identity; threats to cultural security; linguistic and cultural space; kultura; bezpieczeństwo kulturalne; Ukraina; naród; język; narodowa identyczność; zagrożenia kulturalnemu bezpieczeństwu; językowo-kulturalna przestrzeń